Dopamine nation : finding balance in the age of indulgence - Lembke, Anna, 1967- (Dutton, an imprint of Penguin Random House LLC, 2021)
We are living in a time of unprecedented access to high-reward, high-dopamine stimuli: drugs, food, news, gambling, shopping, gaming, texting, sexting. The smartphone is the modern-day hypodermic needle, delivering digital dopamine 24/7 for a wired generation. Lembke explores new scientific discoveries that explain why the relentless pursuit of pleasure leads to pain-- and what to do about it. She illustrates how finding contentment and connectedness means keeping dopamine in check. The secret to finding balance is combining the science of desire with the wisdom of recovery. -- adapted from jacket